Direct medial approach in surgical fixation of fractures in the posterior aspect of the medial malleolus - Chay‐You, Ang; Zhixing Marcus, Ling; Joyce Suang‐Bee, Koh; Tet‐Sen, Howe (Clinical anatomy (New York, N.Y.), 2018)
Fractures in the posterior aspect of the medial malleolus form an important subset of ankle fractures and the indications for fixation include involvement of > 25% of the articular surface or an articular step off by > 2 mm. Several approaches have been described but there has been no recent study on the direct medial approach. Five fresh frozen cadaveric ankles were dissected using the direct medial approach. A longitudinal incision of 10 cm was centered directly over the medial malleolus and deepened straight down to the bone. The periosteum was identified over the distal tibia and careful subperiosteal dissection yielded access to the posterior aspect of the medial malleolus. We investigated the relationship of the neurovascular bundle to the incision by measuring the distance from the center of the medial malleolus to the closest aspect of the bundle. The mean distance from the center of the medial malleolus to the neurovascular bundle was only 2.64 cm (95% CI: 2.06 to 3.22 cm). We found that the neurovascular bundle could be avoided if a periosteal sheath was developed during the dissection and elevated off the posterior aspect of the medial malleolus. The direct medial approach can be performed safely by creating a periosteal sheath through subperiosteal dissection, and the distance of the neurovascular bundle from the incision allows for a good margin of safety during surgery. This approach can be extended proximally and distally and the medial malleolus can be fixed concurrently. Clin. Anat. 31:605–607, 2018. © 2017 Wiley Periodicals, Inc.